Risk Factors for Non-Carbapenemase-Producing Carbapenem-Resistant Enterobacterales Infections: A Retrospective Cohort Study - Sayaka Mabuchi; Tsukasa Nakamura; Toshihiro Imada; Junji Mashino; Takeshi Morimoto (Geriatrics)
Background/Objectives: Carbapenem-resistant Enterobacterales (CRE) infections are widespread, and the risk factors for carbapenemase-producing CRE (CP-CRE) infections are known. Non-CP-CRE (NCP-CRE) infections occur frequently; however, the associated risk factors remain elusive. Therefore, we investigated the risk factors for NCP-CRE infections, especially those caused by Enterobacter and Citrobacter species. Methods: We conducted a retrospective cohort study of patients aged ≥ 18 years with Enterobacter or Citrobacter infections who were admitted to the Department of General Medicine of a tertiary care hospital in Japan from October 2014 to September 2020. We used the data at first detection and performed univariate and multivariate logistic regression analyses to assess the associations between NCP-CRE infections and risk factors such as patient characteristics and antibiotics. Results: In total, 1416 participants were evaluated. The mean age of the patients was 74 ± 17 (range: 18–107) years, of whom 746 (53%) were men. Past use of antibiotics (≥4 days before specimen collection) was not significantly associated with NCP-CRE infections (133 [84%] vs. 1034 [82%], p = 0.5); however, recent use (≤3 days before sample collection) was significantly associated with NCP-CRE infections (42 [27%] vs. 245 [19%], p = 0.036). In the multivariate logistic model, recent use of antibiotics (odds ratio: 1.50, 95% confidence interval: 1.03–2.18) was an independent risk factor for NCP-CRE infections. Conclusions: NCP-CRE infection may be associated with recent antibiotic exposure, but not with the host’s immune status. Therefore, alternative risk factors for NCP-CRE infection may exist.